Physicochemical, potential nutritional, antioxidant and health properties of sesame seed oil: a review - Oboulbiga, Edwige Bahanla; Douamba, Zoénabo; Compaoré-Sérémé, Diarra; Semporé, Judith Nomwendé; Dabo, Rasmata; Semde, Zénabou; Tapsoba, Fidèle Wend-Bénédo; Hama-Ba, Fatoumata; Songré-Ouattara, Laurencia T.; Parkouda, Charles; Dicko, Mamoudou H. (Frontiers in Nutrition, 2023)
Sesame (Sesanum indicum L.) is the oldest annual oilseed grown in Africa and Asia. Sesame seed oil is of great economic and industrial interest worldwide. It is used as a biological resource due to its high content of polyunsaturated, monounsaturated fatty acids and phytochemical antioxidants. It contains bioactive compounds such as lignans (sesamin, sesamol, sesamolin), tocopherols and phytosterols. Its oleic/linoleic ratio makes it important for human health. The levels of bioactive compounds in sesame oil make it valuable for helping to prevent certain cardiovascular, metabolized, and coronary diseases. The ω-3 and ω-6 fatty acids in sesame seed oil are precursors to eicosanoids that regulate the immune system and inflammatory functions. The acids contained in this oil are essential for cell construction and highly recommended during the first trimester of pregnancy. The consumption of sesame seed oil allows a decrease in the LDL-cholesterol complex and together with an increase in the HDL-cholesterol complex. It regulates blood sugar and may have favorable effects on people with liver cancer developing fatty liver disease. In this review, the nutritional value, antioxidant properties, health benefits, and nutrition of sesame seed oil have been compiled to provide collective information of nutritional and medical interest.